Chapter 6 Disability and Human Rights - Series, Lucy (Taylor & Francis, 2019)
This fully revised and expanded second edition of the Routledge Handbook of Disability Studies takes a multidisciplinary approach to disability and provides an authoritative and up-to-date overview of the main issues in the field around the world today. Adopting an international perspective and arranged thematically, it surveys the state of the discipline, examining emerging and cutting-edge areas as well as core areas of contention. Disability studies and different life experiences, examining how disability and disability studies intersects with ethnicity, sexuality, gender, childhood and ageing. Containing 15 revised chapters and 12 new chapters from an international selection of leading scholars, this authoritative handbook is an invaluable reference for all academics, researchers, and more advanced students in disability studies and associated disciplines such as sociology, health studies and social work.